2018
DOI: 10.1159/000495742
|View full text |Cite
|
Sign up to set email alerts
|

Use and Impact of the 21-Gene Recurrence Score in Relation to the Clinical Risk of Developing Metastases in Early Breast Cancer Patients in the Netherlands

Abstract: Background: The nationwide use of the 21-gene recurrence score (21-RS) and implications regarding chemotherapy administration in relation to clinical risk in early breast cancer patients are investigated. Methods: Breast cancer patients surgically treated between 2014 and 2016 were selected from the Netherlands Cancer Registry and categorized as having a clinical low, intermediate, or high risk of developing metastases. Deployment of the 21-RS is advocated in patients with an intermediate risk of developing me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The Dutch clinical risk criteria (low-risk definition: age > 35 years and [grade 1 with tumor ≤3cm, grade 2 with tumor ≤2cm, or grade 3 with tumor ≤1cm]) and the modified Adjuvant! Online criteria have been used in clinical risk stratification for both the MammaPrint and Oncotype DX ® [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Dutch clinical risk criteria (low-risk definition: age > 35 years and [grade 1 with tumor ≤3cm, grade 2 with tumor ≤2cm, or grade 3 with tumor ≤1cm]) and the modified Adjuvant! Online criteria have been used in clinical risk stratification for both the MammaPrint and Oncotype DX ® [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may be argued that the introduction of gene expression assays will reduce the provision of chemotherapy, thereby reducing the costs to justify a potential worse patient outcome. However, chemotherapy decision making studies in the relevant patient group have reported both increased [44][45][46][47] and decreased [48][49][50][51] administration of chemotherapy when gene expression assay results are provided, and none of these studies had a randomised design. Also, from an ethical perspective, withholding an established treatment may be more problematic than introducing a new one.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 21-gene assay can guide treatment-related decision for patients with breast cancer. [21][22][23] St. Gallen International Expert Consensus also has great benefits for treatment-related decision in patients with cancer. 24 Our study confirmed these advantages for treatment-related decision in patients with early-stage invasive breast cancer.…”
Section: Discussionmentioning
confidence: 99%